1991
DOI: 10.1111/j.1600-0722.1991.tb01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries incidence after topical application of varnishes containing different concentrations of sodium fluoride: 3‐year results

Abstract: Abstract— Previous studies have shown that topical application of the fluoride varnish Duraphat reduces caries incidence. The aim of the present study was to compare the caries inhibiting effect of a new fluoride varnish (Carex) containing 1.8% fluoride (F) with that of Duraphat (2.26%F). Informed consent was obtained from the guardians of 495 children 10‐12 yr old in Voss Dental Health District (low F area). The children were randomly allocated to two groups. One group of subjects received 6‐monthly applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Hence, these re sults are in agreement with the findings of Hagan and Bawden [1985] who applied full-and half-strength acidulated phosphate fluoride gel in ll-to 15-year-old children. The results of Seppa et al [1994] in 12-to 14-year-old children showed a similar caries-preventive effect of sodium fluoride varnish (Duraphat) containing either 2.3% or 1.1% F. Fur thermore, the lowering of the fluoride content of a varnish (Duraphat) from 2.3 to 1.8% (an experimental sodium fluo ride varnish) did not adversely affect the caries incidence in the study performed by Haugejorden and Nord [1991], while even lower concentrations have inhibited enamel dis solution and promoted remineralization in vitro [ten Cate, 1990] or in vivo [Goorhuis and Purdel-Lewis, 1986], In the present study, only the 0.25% amine fluoride solution was less effective than higher concentrations (0.5 and 1% F).…”
Section: Discussionmentioning
confidence: 51%
“…Hence, these re sults are in agreement with the findings of Hagan and Bawden [1985] who applied full-and half-strength acidulated phosphate fluoride gel in ll-to 15-year-old children. The results of Seppa et al [1994] in 12-to 14-year-old children showed a similar caries-preventive effect of sodium fluoride varnish (Duraphat) containing either 2.3% or 1.1% F. Fur thermore, the lowering of the fluoride content of a varnish (Duraphat) from 2.3 to 1.8% (an experimental sodium fluo ride varnish) did not adversely affect the caries incidence in the study performed by Haugejorden and Nord [1991], while even lower concentrations have inhibited enamel dis solution and promoted remineralization in vitro [ten Cate, 1990] or in vivo [Goorhuis and Purdel-Lewis, 1986], In the present study, only the 0.25% amine fluoride solution was less effective than higher concentrations (0.5 and 1% F).…”
Section: Discussionmentioning
confidence: 51%
“…Anticaries efficacy of low-fluoride professional preparations (gel, varnishes) has also been shown in some other clinical studies [Hagan et al, 1985;Haugejorden and Nord, 1991;Seppä et al, 1994]. However, in individuals with poor oral hygiene and severe plaque accumulation, fluoride agents may have a limited cariostatic potential and no dose-response relationship could be observed.…”
Section: Discussionmentioning
confidence: 97%
“…The guardians of 495 children 10 to 12 years of age @om 1973-75) living at Voss (<0.05mg FA in the drinking water) gave written informed consent for their dependents to participate in an F varnish study (22).…”
Section: Matmalsmentioning
confidence: 99%